2020
DOI: 10.1016/j.acra.2020.04.033
|View full text |Cite
|
Sign up to set email alerts
|

CT Manifestations and Clinical Characteristics of 1115 Patients with Coronavirus Disease 2019 (COVID-19): A Systematic Review and Meta-analysis

Abstract: Rationale and Objectives: We aimed to assess the prevalence of significant computed tomographic(CT) manifestations and describe some notable features based on chest CT images, as well as the main clinical features of patients with coronavirus disease 2019(COVID-19). Materials and Methods: A systematic literature search of PubMed, EMBASE, the Cochrane Library, and Web of Science was performed to identify studies assessing CT features, clinical, and laboratory results of COVID-19 patients. A single-arm meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
3
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 42 publications
9
68
3
8
Order By: Relevance
“…Various findings can be seen in the lung parenchyma in COVID-19 infection (15). The most common of these is the ground-glass appearance, defined as an increase in fog-shaped density in which the walls of the vessels and bronchi are not wiped (16,17). It develops due to mild interstitial thickening or air loss within the airways (18).…”
Section: Discussionmentioning
confidence: 99%
“…Various findings can be seen in the lung parenchyma in COVID-19 infection (15). The most common of these is the ground-glass appearance, defined as an increase in fog-shaped density in which the walls of the vessels and bronchi are not wiped (16,17). It develops due to mild interstitial thickening or air loss within the airways (18).…”
Section: Discussionmentioning
confidence: 99%
“…Many patients who are hospitalized due to COVID-19 get multiple chest CT scans depending on the clinical progression. There are a few series in the literature that have demonstrated how evolution of thoracic imaging findings happen [2,11,20]. In spite of the commonly observed chest imaging findings associated with COVID-19, reports of abdominal imaging findings are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Older age, comorbidities including hypertension, diabetes, cardiovascular disease, respiratory disease, and laboratory examinations such as white blood cells (WBC), aspartate aminotransferase (AST), creatinine, lactate dehydrogenase (LDH), and d-dimer have been reported to imply the progression of COVID-19 [9,10]. Chest CT findings have been shown to be associated with severe or critical COVID-19 pneumonia as well as with the different stages of the disease [11,12]. Although the involvement of the respiratory system is common, liver injury may occur especially in patients with severe COVID-19 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary involvement of COVID-19 predominantly manifest as subpleural ground glass opacities and consolidation. Early identification of typical CT findings provides timely diagnostic evidence of the disease and enables early decision-making and treatment ( 16 , 17 ). In this study, we observed a strong positive correlation between number of daily positive CT scans and daily PCR-confirmed COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%